2017
DOI: 10.1093/nop/npw028
|View full text |Cite
|
Sign up to set email alerts
|

Quality of survival and cognitive performance in children treated for medulloblastoma in the PNET 4 randomized controlled trial

Abstract: Background:The relationship between direct assessments of cognitive performance and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…High-risk medulloblastoma is associated with a 5-year, event-free survival (EFS) of about 60% [ 6 , 7 , 8 , 9 , 10 , 11 ]. Moreover, those patients that are cured have significant long-term toxicities (including neurocognitive and endocrinological toxicities) [ 12 , 13 , 14 ]. The median intelligence quotient (IQ) following therapy for medulloblastoma is in the order of 80 with significant effects on processing speed.…”
Section: High-risk Medulloblastoma: Background Challenges and Basis For Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-risk medulloblastoma is associated with a 5-year, event-free survival (EFS) of about 60% [ 6 , 7 , 8 , 9 , 10 , 11 ]. Moreover, those patients that are cured have significant long-term toxicities (including neurocognitive and endocrinological toxicities) [ 12 , 13 , 14 ]. The median intelligence quotient (IQ) following therapy for medulloblastoma is in the order of 80 with significant effects on processing speed.…”
Section: High-risk Medulloblastoma: Background Challenges and Basis For Clinical Trialsmentioning
confidence: 99%
“…In many cases, independent living will not be possible and the ability to hold down a job unlikely. Initial studies indicate the severity of toxicity and late effects may be associated with the treatment received, clinico-biological disease features, and host genetic factors [ 7 , 12 ].…”
Section: High-risk Medulloblastoma: Background Challenges and Basis For Clinical Trialsmentioning
confidence: 99%
“…[5][6][7][8][9] Long-term sequelae seem to be dose-and age-dependent, leading to efforts to dose deescalate and defer PORT in young children. 5,6,9,10 Historically, CSI dose deescalation was found to be associated with poorer disease control and survival compared with standard-dose CSI to 36.0 Gy. 11 However, when combined with the use of cisplatin-based multiagent chemotherapy, CSI dose deescalation has yielded outcomes comparable with those of historical controls treated with standard-dose CSI.…”
mentioning
confidence: 99%
“…A review that assessed 20 studies examining the association between performance-based and questionnaire-based measures of EF concluded that those measures probably assess different underlying mental constructs (Toplak, West, & Stanovich, 2013). In addition, inconsistencies have been reported between normal performance on cognitive tests contrasting with profound deficits in EFs in daily life activities (Câmara-Costa et al, 2017;Chevignard, Catroppa, Galvin, & Anderson, 2010). Data from proxy-reports have advantages but also carry their limitations.…”
Section: Abi During Childhood Can Be Associated With Enduring Difficumentioning
confidence: 99%